Clinical Teaching Confidence, Competence and Effectiveness Among Nurse Preceptors: A Structural Equation Model - Idala, Lisette (MALATA SAINS INDONESIA, 2025)
Introduction: Clinical teaching is an essential component in nursing education in bridging theory and practice. Nurse preceptors play vital role in guiding nursing interns in clinical practice. Objectives: Study aimed to examine the relationship between the perceived levels of confidence, competence, and effectiveness of clinical teaching among nurse preceptors in government hospitals in the southern region of Saudi Arabia. Methods: The method used in the study was descriptive quantitative correlation design. Data were collected electronically utilizing adopted questionnaires. Covariance-based structural equation modeling (CB-SEM), using maximum likelihood estimation was conducted to analyze the interrelationships between and among clinical teaching confidence, competence, and effectiveness. Results: The dimensions of confidence and competence in clinical teaching were correlated with one another, with correlation coefficients (r-value) ranging from 0.22 to 0.33, and p-value of 0.003. In a similar vein, confidence had moderate to high linear associations with effectiveness in clinical teaching, with correlation coefficients (r-value) varying from 0.24 to 0.44, β=0.48, p=0.004. In contrast, findings showed that the correlation coefficients (r-value) ranged from 0.01 to 0.17 for the competence and effectiveness in clinical teaching, and were not statistically significant (β=–0.06, p=0.591). Conclusions: Clinical teaching confidence significantly influences effectiveness, while competence alone does not guarantee teaching quality. Although many nurse preceptors are skilled clinicians, they may lack formal teaching expertise. Structured training programs that strengthen pedagogical skills and emphasize effective clinical teaching practices are recommended to enhance preceptor effectiveness and support the development of students’ clinical competency.